Confidence bands for impulse responses: Bonferroni versus Wald - Helmut Lütkepohl; Anna Staszewska-Bystrova; Peter Winker (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
In impulse response analysis estimation uncertainty is typically displayed by constructing bands around estimated impulse response functions. These bands may be based on frequentist or Bayesian methods. If they are based on the joint distribution in the Bayesian framework or the joint asymptotic distribution possibly constructed with bootstrap methods in the frequentist framework often individual con dence intervals or credibility sets are simply connected to obtain the bands. Such bands are known to be too narrow and have a joint con dence content lower than the desired one. If instead the joint distribution of the impulse response coefficients is taken into account and mapped into the band it is shown that such a band is typically rather conservative. It is argued that a smaller band can often be obtained by using the Bonferroni method. While these considerations are equally important for constructing forecast bands, we focus on the case of impulse responses in this study.
Keywords: C32; 330; Impulse responses; Bayesian error bands; frequentist con dence bands; Wald statistic; vector autoregressive process